2021
DOI: 10.1371/journal.pone.0257570
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic and demographic determinants of fertility in six selected Pacific Island Countries: An empirical study

Abstract: In this study, we seek to perform macro analysis of fertility in a panel of 6 selected Pacific Island Countries (PICs, hereafter). The macro analysis with secondary data, mostly obtained from World Bank database, stretched over the period 1990–2019 was stacked randomly in a balanced panel set-up, within which the most preferred fixed effect model is used for multivariate analysis. Pooled OLS and Random effect estimation techniques were applied for comparing results. Categories such as women’s empowerment, heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The analysis identified among other factors that urbanization has played an influential role in attitudinal change in favour of small family size. Investigating socioeconomic determinants of fertility decision in Pacific Island countries recently, Lal et al (2021) found that urbanization amongst other factors account for decline in fertility in the region.…”
Section: Empirical Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The analysis identified among other factors that urbanization has played an influential role in attitudinal change in favour of small family size. Investigating socioeconomic determinants of fertility decision in Pacific Island countries recently, Lal et al (2021) found that urbanization amongst other factors account for decline in fertility in the region.…”
Section: Empirical Literaturementioning
confidence: 99%
“…To investigate the possible relationship between urbanization process and female decision to give birth in Nigeria and South Africa, we used annual data collected between 1981 and 2019. Following notable research which had investigated the macroeconomic determinants of fertility rates such as Amarante (2014), Khan and Tehseen (2017), Kashepoor (2018) and Lal et al (2021, we proxy the dependent variable as total fertility rate (TFR) while we adopted urban population growth rate as a measure of degree of urbanization. In order to avoid estimation error that may arise from misspecification of regression model, empirical analyses of cause-effect relationship must control for the effect of other variables that may be correlated with the dependent variable.…”
Section: Data and Variablesmentioning
confidence: 99%
“…The literature reveals that fertility is influenced by various factors, including social, economic, demographic, and cultural aspects. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 It is evident that the empowerment of women is a robust predictor of fertility in developed and developing countries. 27 , 28 , 29 According to Zeba and Kazi 30 who examined the data of 1036 Pakistani women, mobility was positively correlated with births within the last 5 years but negatively correlated with cumulative fertility.…”
Section: Introductionmentioning
confidence: 99%